THE PARTICIPATION OF PARENTS IN THE ACADEMIC MANAGEMENT OF ELEMENTARY SCHOOL,: THE PROMOTE EFFECTIVE MANAGEMENT OF THE 6 IN AREA 1 FROM THE OFFICE OF PRIMARY EDUCATON, PATHUMTHANI - ไชยเสริฐ, สินทัย; งามประโคน, สิน; ฐิตวฑฺฒโน, พระมหาญาณวัฒน์ (Journal of Educational Review Faculty of Education in MCU, 2019)
This research’s objectives were 1) to study the participation of students’ parents in administrating the schools in the sixth group of network to promote the effectiveness of educational management in area 1 from the office of Primary Education, Pathumthani, 2) to compare it and 3) to present its ways. The sample was used to study in this research. There were the students’ parents at primary 4 in in the sixth group of network to promote the effectiveness of educational management in area 1 from the office of Primary Education Pathumthani. They were 256 persons in the eleven schools. The questionnaires were the standard and the statistic program was used as the frequency, the percentage, the means and the standard deviation Z-test, F-test (One-way ANOVA), Fisher’s LSD. Findings were as follows: Their participation was found that it was at high level both in the overview and issues that are 1) the item of curriculum development, 2) the item of measure and evaluation, 3) the item of learning atmosphere and 4) the item of innovational media promotion and development. Its comparison was found that it was not difference in the overview. Each issue was found that it was significantly statistic difference with at 0.05. There were five numbers of issues that are the curriculum development, the learning management, the learning resource promotion, the educational quality promotion and the measure and evaluation. The suggestions would be presented in this title of research consisting of the issues. There are 1) the item of learning resources what would be made them ready and multiple, 2) the item of learning atmosphere which would be designed the classrooms or places properly to learn in the schools, 3) the item of learning would be added to teach in overtime or after completed learning, 4) the item of measure and evaluation would have the participation by their parents, 5) the item of an educational quality promotion would be supported and participated by their parents in many activities, 6) the item of curriculum development would be participated by their parents and 7) the item of an innovational media development would be used every time when teachers were teaching in the classroom.